Accuracy of Maternal Substance Use History Among Infants at Risk of Neonatal Abstinence Syndrome [02O]. (May 2020) - Humphreys, Meredith; Smid, Marcela Carolina; Gavin, Erin; Fung, Camille; Johnson, Erin; Allshouse, Amanda A.
Abstract : INTRODUCTION: Prenatal substance exposure increases risk of neonatal abstinence syndrome (NAS). The objective of this study was to determine the concordance between documented maternal substance use history and neonatal results among mother-infant dyads at risk of NAS. METHODS: We performed a retrospective chart review of mother-infant dyads at risk for NAS, defined as those infants receiving neonatal withdrawal inventory scores. We included those dyads with available maternal charts and infant biological testing (meconium or cord toxicology results). Maternal substance use defined as maternal reported use or positive urine toxicology. We excluded multiple gestation and preterm infants (<37 weeks). We calculated positive predictive value (PPV), negative predictive value (NPV) and accuracy of maternal history of opioid, stimulant, marijuana and anti-depressant use with infant biological results. IRB approval was obtained. RESULTS: From May 2017–May 2018, 197 dyads met study criteria. Maternal opioid history (n=135, 69%) had PPV 83.7% (95% CI 78.6–87.8%), NPV 56.5% (95% CI 46.6–65.8%) and accuracy 75.1% (95% CI 68.5–81%). Maternal stimulant history (n=91, 46%) had PPV 58.2% (95% CI 51.2–64.9%), NPV 94.3% (95% CI 88.6–97.3%) and accuracy 77.6% (95% CI 72.2–83.3%). Maternal marijuana history (n=65, 33%) had PPV 42.4% (95% CI 35.7–49.3) and accuracy 80.7% (95% CI 74.5–85.9%) (NPV could not be calculated). Maternal anti-depressant history (n=52, 26%) had PPV 59.0% (95% CI 47.2–70.0%), NPV 99.4% (95% CI 95.8–99.9%) and accuracy 91.4% (95% CI 86.5–94.9%). CONCLUSION: Maternal history and infant biological testing accuracy varies by substance and may miss up to a quarter of infants at risk of NAS. Improved screening procedures for maternal substance use are needed.